2020
DOI: 10.2196/18155
|View full text |Cite
|
Sign up to set email alerts
|

Association of eHealth Literacy With Lifestyle Behaviors in University Students: Questionnaire-Based Cross-Sectional Study

Abstract: Background Maintenance of good health and a healthy lifestyle have significant impacts on the lives of university students. However, university students are prone to engage in risky health behaviors, resulting in impaired health status. Electronic health (eHealth) literacy is an important factor in maintaining a healthy lifestyle. However, no studies have assessed the eHealth literacy levels and the associated lifestyle behaviors among university students in Japan. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
48
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 46 publications
(91 reference statements)
11
48
2
Order By: Relevance
“…This study indicates that duration of daily internet use is associated with a willingness to adopt mHealth among parents, which is in line with a previous study that reported time spent on the internet is greatly associated with the level of eHealth literacy [30,31]. However, time spent on the internet was reported to be a nonsignificant factor in other studies; therefore, the small sample size and methodological differences may have played an important role in it [32,33].…”
Section: Principal Findingssupporting
confidence: 88%
See 1 more Smart Citation
“…This study indicates that duration of daily internet use is associated with a willingness to adopt mHealth among parents, which is in line with a previous study that reported time spent on the internet is greatly associated with the level of eHealth literacy [30,31]. However, time spent on the internet was reported to be a nonsignificant factor in other studies; therefore, the small sample size and methodological differences may have played an important role in it [32,33].…”
Section: Principal Findingssupporting
confidence: 88%
“…Results from the bivariate analyses demonstrated that age, interest in the pandemic, the source that recommended mHealth, the presence of a chronic disease in children, duration of daily internet use, and use of mHealth before the COVID-19 outbreak were associated with willingness to adopt mHealth during the pandemic. The multivariate logistics regression model indicated that the parents' age (26)(27)(28)(29)(30)(31)(32)(33)(34)(35) The odds of being willing to adopt mHealth were 8.1 times greater in parents aged from 26 to 35 years than parents aged from 18 to 25 years (P=.02). The odds of being willing to adopt mHealth were 8.6 times greater in respondents with moderate interest in the pandemic than respondents with low interest (P=.004).…”
Section: Factors Associated With Willingness To Adopt Mhealthmentioning
confidence: 99%
“…Researchers have attributed this association to risk perception; COVID-19 pandemic information on the internet exacerbates concerns and may prompt users to adopt protective behaviors [ 45 ]. Further, a related study of college students reported that their eHealth literacy is associated with regular exercise, healthy eating, and routine sleep [ 46 ]. Moreover, a study found that eHealth literacy is related to disease prevention behaviors, such as finding vaccination information [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though people with chronic had strong desire to seek for health information on the internet for medication information, nutrition, disease management and prevention actions, and so on. It has reported that those who rated their health as good or excellent had signi cantly higher eHEALS scores than those who rated their health as fair or poor [34]. In addition, participants in the high eHEALS scores group exercised more frequently than those in the low score group.…”
Section: Discussionmentioning
confidence: 99%